Potential anti-osteoporotic effect of Allolobophora caliginosa extract in orchiectomized rats - Ayat Youssef; Ahmed Baiomy; Sohair Ramadan Fahmy; Ayman Mohamed; Dalia Saad; Reham Desoky (Faculty of Pharmacy, Mahidol University, 2022)
Osteoporosis is defined as a universal skeletal disorder. The medicinal importance of earthworms has been known from time immemorial. The present investigation was designed to assess the antiosteoporotic efficacy of the earthworm, Allolobophora caliginosa extract (AcE) in bilaterally orchiectomized rats (OCX) to elicit the underlying in vivo mechanism. Twenty-eight male rats were divided into two groups. The first group (7 rats/group) represented sham-operated rats, while the second group (21 rats/group) underwent bilateral orchidectomy (OCX). The second group was randomly subdivided into three subgroups; OCX and A. caliginosa extract (AcE) (100 or 200 mg/kg body weight/day) treated subgroup. Administration of AcE to OCX rats increased femoral bone mineral density (BMD), bone mineral content (BMC), calcium (Ca), phosphorus (P), and calcitonin level, as compared to OCX rats. On the other hand, administration of AcE to OCX rats significantly decreased serum alkaline phosphatase (ALP) activity and parathyroid hormone (PTH) level compared to OCX rats. The present study showed that AcE is a beneficial novel natural antiresorptive agent. Its anti-osteoporotic effects may positively impact osteoblast differentiation, particularly bone mineralization, and higher osteoblast activity account for bone formation, preventing osteoporosis.